Sir William Jones (1746–1794) and the Early Orientalist Discourse on Sufism - Ahmad Munji; Hasyim Muhammad (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
Many theories have been proposed to discuss Sufism in terms of its linguistic origins and its role in spiritual knowledge, its concepts and ideas, and cultural influences. Both Muslim and orientalist scholars have offered opposing views on the beginnings of Sufism. Unfortunately, Western orientalists were the first to research this topic, and their ideas greatly influenced later scholars. This study examines how early British orientalists, particularly Sir William Jones, approached the study of Sufism. Jones represents the early development of British orientalism, which started in the form of personal travel accounts long before orientalist societies were established to support them. Only the later ‘experts on the Orient’ created scholarly circles that followed a more objective and systematic approach to studying Muslim cultures, yet often persisted in the erroneous claim that Sufism was an external and foreign element in Islamic culture.